Design of redundant microvascular cooling networks for blockage tolerance. (25th February 2018) - Pety, Stephen J.; Tan, Marcus Hwai Yik; Najafi, Ahmad R.; Gendusa, Anthony C.; Barnett, Philip R.; Geubelle, Philippe H.; White, Scott R.
Highlights: For the first time, microchannel networks are optimized to tolerate blockages. Optimized cooling panels show reduced temperature rise when a channel is blocked. Blockage tolerance increases further for networks with higher nodal degree. Temperature rise values range from 7 °C (optimized) to 35 °C (reference). A new high-speed fabrication technique is used to validate the optimized designs. Abstract: Microvascular networks can provide host materials with many functions including self-healing and active cooling. However, vascular networks are susceptible to blockage which can dramatically reduce their functional performance. A novel optimization scheme is presented to design networks that provide sufficient cooling capacity even when partially blocked. Microvascular polydimethylsiloxane (PDMS) panels subject to a 2000 W m −2 applied heat flux and 28.2 mL min −1 coolant flow rate are simulated using dimensionally reduced thermal and hydraulic models and an interface-enriched generalized finite element method (IGFEM). Channel networks are optimized to minimize panel temperature while the channels are either clear (the O 0 scheme), subject to the single worst-case blockage ( O 1 ), or subject to two worst-case blockages ( O 2 ). Designs are optimized with nodal degree (a measure of redundancy) ranging from 2 to 6. The results show that blockage tolerance is greatly enhanced for panels optimized while considering blockages and for panels with higher nodal degree. For example, the 6-degree O 1 design only has a temperature rise of 7 °C when a single channel is blocked, compared to a 35 °C rise for the 2-degree O 0 design. Thermography experiments on PDMS panels validate the IGFEM solver and the blockage tolerance of optimized panels.